(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT This research came to shed light on forgetfulness in the lives of the prophets and the righteous.. The prophets are human beings who may forget as a human in matters that are not related to legislation and notification because they are infallible from forgetting then, and it may happen in the life of the righteous as well, which is due to a mistake and negligence. As for the treatment of human forgetfulness, it is through adherence to the Noble Qur’an, frequent remembrance of Allah Almighty, leaving the gatherings of the oppressors, taking good company that helps a person to remember, and praying to Allah to forgive him what he forgots.